Comparison of short-segment monoaxial and polyaxial pedicle screw fixation combined with intermediate screws in traumatic thoracolumbar fractures: a finite element study and clinical radiographic review (Clinics, 2017)
OBJECTIVES: No studies have compared monoaxial and polyaxial pedicle screws with regard to the von Mises stress of the instrumentation, intradiscal pressures of the adjacent segment and adjacent segment degeneration. METHODS: Short-segment monoaxial/polyaxial pedicle screw fixation techniques were compared using finite element methods, and the redistributed T11-L1 segment range of motion, largest maximal von Mises stress of the instrumentation, and intradiscal pressures of the adjacent segment under displacement loading were evaluated. Radiographic results of 230 patients with traumatic thoracolumbar fractures treated with these fixations were reviewed, and the sagittal Cobb’s angle, vertebral body angle, anterior vertebral body height of the fractured vertebrae and adjacent segment degeneration were calculated and evaluated. RESULTS: The largest maximal values of the von Mises stress were 376.8 MPa for the pedicle screws in the short-segment monoaxial pedicle screw fixation model and 439.9 MPa for the rods in the intermediate monoaxial pedicle screw fixation model. The maximal intradiscal pressures of the upper adjacent segments were all greater than those of the lower adjacent segments. The maximal intradiscal pressures of the monoaxial pedicle screw fixation model were larger than those in the corresponding segments of the normal model. The radiographic results at the final follow-up evaluation showed that the mean loss of correction of the sagittal Cobb’s angle, vertebral body angle and anterior vertebral body height were smallest in the intermediate monoaxial pedicle screw fixation group. Adjacent segment degeneration was less likely to be observed in the intermediate polyaxial pedicle screw fixation group but more likely to be observed in the intermediate monoaxial pedicle screw fixation group. CONCLUSION: Smaller von Mises stress in the pedicle screws and lower intradiscal pressure in the adjacent segment were observed in the polyaxial screw model than in the monoaxial pedicle screw fixation spine models. Fracture-level fixation could significantly correct kyphosis and reduce correction loss, and adjacent segment degeneration was less likely to be observed in the intermediate polyaxial pedicle screw fixation group.